1982
DOI: 10.1136/thx.37.7.532
|View full text |Cite
|
Sign up to set email alerts
|

Rigid bronchoscopy under intravenous general anaesthesia with oxygen Venturi ventilation.

Abstract: In a study of 100 patients undergoing rigid bronchoscopy under intravenous general anaesthesia with oxygen Venturi ventilation no major complications were observed. Minor complications included one adverse reaction to alphaxalone-alphadolone acetate (Althesin), one prolonged episode of laryngeal spasm after removal of the bronchoscope, and subsequent muscle pain attributed to suxamethonium in 36 patients. The last complication occurred significantly less frequently (p < 0-025) in those patients who were pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…This may induce translocation of bacteria or endotoxins to systemic circulation and organs [23]. Rigid bronchoscopic procedures have been shown to induce alterations in arterial blood gases including acidosis, hypoxaemia, and hypercarbia [24,25]. Likewise, the current study found a decrease in pH and Pa,O 2 and an increase in Pa,CO 2 values following bronchoscopy in rats.…”
Section: Discussionsupporting
confidence: 63%
“…This may induce translocation of bacteria or endotoxins to systemic circulation and organs [23]. Rigid bronchoscopic procedures have been shown to induce alterations in arterial blood gases including acidosis, hypoxaemia, and hypercarbia [24,25]. Likewise, the current study found a decrease in pH and Pa,O 2 and an increase in Pa,CO 2 values following bronchoscopy in rats.…”
Section: Discussionsupporting
confidence: 63%
“…There may some reports indicating that rigid bronchoscopy does not impair ventilation and oxygenation [2]. However, what about clinical studies that do show that rigid bronchoscopy induces alterations in arterial blood gases, including hypoxaemia, respiratory acidosis and hypercarbia [3][4][5]? GODDEN et al [3] measured serial arterial blood gases in 10 patients during rigid bronchoscopy and showed carbon dioxide retention in nine patients even though ventilation was adequate in all.…”
Section: From the Authorsmentioning
confidence: 99%
“…However, what about clinical studies that do show that rigid bronchoscopy induces alterations in arterial blood gases, including hypoxaemia, respiratory acidosis and hypercarbia [3][4][5]? GODDEN et al [3] measured serial arterial blood gases in 10 patients during rigid bronchoscopy and showed carbon dioxide retention in nine patients even though ventilation was adequate in all. MATHISEN and GRILLO [4] observed 19 complications of 56 patients after rigid bronchoscope, in whom two of those complications were hypoxia and/or hypercarbia.…”
Section: From the Authorsmentioning
confidence: 99%
See 2 more Smart Citations